A versatile method for assessing pathogenicity of Hymenoscyphus fraxineus to ash foliage. Issue 2 (14th December 2018) - Orton, Elizabeth S.; Clarke, Martha; Brasier, Clive M.; Webber, Joan F.; Brown, James K. M.
Abstract: We describe a method for inoculating rachises of Fraxinus excelsior (European or common ash) with Hymenoscyphus fraxineus, which is faster than previous methods and allows associated foliar symptoms to be assessed on replicate leaves. A total of ten ash seedlings were inoculated with five isolates of H. fraxineus and lesion development assessed over four weeks. A five‐point disease progress scale of symptom development was developed from no lesion (0), lesion on rachis (1), "pre‐top dead, " with curling of distal leaflets and bending of the rachis (2), top dead, with wilting and death of distal leaflets (3) to leaf abscission (4). The method revealed variation in aggressiveness of H. fraxinus isolates and may be suitable for assessing the resistance of F. excelsior and other Fraxinus species to dieback. The in vitro growth rate of H. fraxineus isolates was highly correlated with both disease progress and the length of rachis lesions on susceptible plants, indicating that it can be used as a preliminary step in selecting isolates with high aggressiveness for use in resistance screening.